The Role of Modern Artistic Media in Cultural Discourse with Emphasis on Globalization - Sara Jahangiri; Mohammadreza Sharifzadeh; MohammadKazem Hassanvand (Iranian Journal of Educational Research)
Objective: The contemporary world is characterized by the emergence of new media, marking an era in which media has become an indispensable component of human existence. In today's society, the pervasive presence of novel communication technologies has bestowed significance upon various facets of life. Notably, new forms of artistic media hold a crucial position in the realm of art education and the advancement of culture. Modern artistic media, encompassing video art, layout, photography, conceptual art, digital art, performance art, and more, play a particularly pivotal role in the realms of education, presentation, and the introduction of artistic works and culture within society. This research endeavors to examine the role of new artistic media in cultural education and the promotion of urban society, aiming to address the following question: How do new artistic media contribute to cultural education and the advancement of urban society? The objective of this article is to enhance our understanding of modern artistic media and evaluate their efficacy within the realm of education and culture in society. Methods: Employing a descriptive-analytical research method, this study relies on library and documentary sources for data collection. Results: The findings indicate that, facilitated by technological advancements and the ability to reproduce artworks, new media possess the potential to exert a significant impact on education and culture within society. This research can serve as a valuable tool in increasing the visibility and public awareness of new artistic media, thereby fostering improvement within urban societies. Conclusions: By recognizing the capabilities of new artistic media, we can progress towards the production and development of culture, education, and the overall prosperity of society.